Effect of initial microstructure on the evolution of texture in AA 3004 sheets during continuous confined strip shearing and subsequent annealing - 허무영; 김종국; 정영훈 (Chinese Society of Nonferrous Metal, 2002)
The evolution of texture and microstructure during continuous confined strip shearing (CCSS) and subsequent annealing of aluminum 3004 alloy sheets was investigated by comparing the results of two initial specimens with different initial microstructures but nearly the same initial textures. The tools of CCSS based on the equal channel angular pressing (ECAP) were designed to provide a constant shear deformation of the order of 0.5 per pass while preserving the original sheet shape. Strips of AA 3004 having different initial microstructures were deformed by CCSS up to three passes. FEM results indicated that the shear formation is not homogeneous throughout the sample thickness, in particular at the surface layers. The rolling texture components of the initial specimens decreased during CCSS, and preferred orientations along two fibers were developed. During CCSS and subsequent annealing the texture strongly developed in the softer initial specimen. With an increasing number of CCSS passes, deformation texture did not develop further. The evolution of annealing texture depended on deformation texture. Observations by TEM and EBSD revealed the formation of sub-micrometer sized grains after CCSS.